Peralihan Harta Bersama dalam Perkawinan yang Tidak Dicatatkan - Muhammad Alif Gemail; Anwar Borahima; Nurfaidah Said (Nagari Law Review, 2019)
This study aims to analyze the legal consequences arising from legal actions carried out before a notary by a couple whose marriage is not recorded and legal efforts to protect parties when legal actions occur. This research is a normative legal research using a law and case approach. The location of the study was conducted in Makassar City. The results showed that the legal consequences arising from legal actions carried out before a Notary by a couple whose marriage was not recorded is a Notary Certificate, cannot be made by the Notary because they do not have evidence that confirms that a legal marriage has been carried out. In this case what is meant is the Deed Marriage issued by the Civil Registry Office because the marriage is only done according to their religion and beliefs. Legal measures to protect parties when legal actions occur are the establishment of permits to return the name of the land certificate to the District Court where the object of land / building is located. In the application to the District Court, it should also be requested for the Judge's confirmation in the determination that Mona's mother is the only heir based on a marriage that has been carried out in accordance with religious law and her beliefs